Effect of cordocentesis on fetal myocardial performance - Kasemsri Srisupundit (2018)
© 2016 John Wiley & Sons, Ltd. Objective: To compare fetal Tei index before, immediately after and 30 min after cordocentesis for prenatal diagnosis. Patients and methods: Pregnant women undergoing prenatal diagnostic cordocentesis in the early mid-trimester underwent measurement of the fetal Tei index of both right and left ventricles just before cordocentesis, immediately after and at 30 min after the procedure. Results: A total of 143 singleton women underwent cordocentesis at a median gestational age of 19 weeks (range 16–23). The most common indication was fetal risk of beta-thalassemia/hemoglobin E disease (42%, 60 cases). Immediately after cordocentesis, fetal Tei index and all its components at both ventricles were significantly altered when compared with the baseline values (p < 0.001). At 30 min after cordocentesis, components of the Tei index had significantly improved but 5/6 had not completely recovered. No serious procedure-related short-term complications were observed in the study. Conclusion: Cordocentesis has a negative impact on fetal hemodynamics as indicated by worsening of the Tei index. Although the adverse effect seems to be temporary, the recovery time may be longer than 30 min. © 2016 John Wiley & Sons, Ltd.